Ministerial Decree No. 1082/2017 promulgating the executive regulations of the law on facilitating the procedures of licensing the industrial establishments promulgated by law No. 15/2017 / translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Serial No. 46/2017